Changing the (Magisterial) Subject: Women Teaching-with-Authority—from Vatican II to Tomorrow. (February 2016) - Mannion, Gerard
Pope Francis has stated that 'The challenge [for the church] today is this: to think about the specific place of women also in those places where the authority of the church is exercised for various areas of the church.' Here we have a pope inviting discussion on the role and authority of women in the church. This is a statement with wide-reaching moral and ecclesiological implications. To explore some of these, this paper focuses on 'changing the (magisterial) subject' in a twofold sense. It focuses upon transformations in the understanding of teaching authority and also upon the subjects who exercise such during and since Vatican II. In particular, it explores both topics vis-à-vis the role of women in the church, especially their contributions to the church's exercise of magisterium. It seeks to do so in the main by reflecting upon the women present in an active capacity at Vatican II, who effectively serve as a case study for our considerations of the most pressing questions pertaining to women and magisterium, questions which Pope Francis has clearly brought center-stage once more and seems determined to engage.